IMMUNOCHROMATOGRAPHIC ANALYSIS: ASSESSMENT AND PROSPECTS FOR APPLICATION IN THE DIAGNOSIS OF ROTAVIRUS AND ADENOVIRUS INFECTIONS - Mukantayev , K.; Tursunov, K.; Adish , Zh.; Tarlykov, P. (Eurasian Journal of Applied Biotechnology, 2025)
The objective of this review was to provide information on immunochromatographic assays (ICA) relevant to the diagnosis of human adenovirus (HAdV) and rotavirus (HRV) infections. HAdVs and HRVs cause respiratory and gastrointestinal diseases in children and are characterized by strong inflammatory responses. Virological diagnostic methods include virus isolation in cell cultures, molecular-biological techniques, and immunological assays. These methods are considered the gold standard; however, obtaining results requires a significant amount of time. The development of reverse transcription polymerase chain reaction (RT-PCR) has greatly facilitated the diagnosis of viral infections due to its high specificity and sensitivity. However, the complexity of the reaction protocol and the need for additional laboratory equipment make RT-PCR unsuitable for point-of-care testing. Immunochromatographic analysis, due to its low cost, simple sample preparation, and ease of use, represents an excellent alternative for bedside diagnostics. In studies on other infections, ICA has demonstrated the absence of cross-reactivity, high reproducibility, and acceptable sensitivity compared to enzyme-linked immunosorbent assay (ELISA) and RT-PCR. In conclusion, ICA test systems may be useful in clinical practice for the rapid detection of rotavirus and adenovirus infections. However, the possibility of false-positive results and differences in subtype identification across various diagnostic methods should be taken into account.